2010
DOI: 10.1007/s11002-010-9101-6
|View full text |Cite
|
Sign up to set email alerts
|

Do complainants appreciate overcompensation? A meta-analysis on the effect of simple compensation vs. overcompensation on post-complaint satisfaction

Abstract: Service recovery, Compensation, Meta-analysis, Consumer behavior, Consumer satisfaction, Complaint management,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 50 publications
7
36
0
2
Order By: Relevance
“…In line with this idea, the results of Study 4 revealed that overcompensation is just as effective as equal compensation to promote the preservation of the relationship between the perpetrator and the victim, to increase victims' intentions to cooperate with the perpetrator again in the future, and to entail actual cooperative behavior on the part of the victim. These results also corroborate the findings of a recently conducted meta-analysis in the field of consumer behavior, which demonstrated that overcompensation has no additional effect on post-complaint satisfaction, beyond the impact of simple compensation (Gelbrich & Roschk, 2011).…”
Section: Economic and Psychological Perspectivessupporting
confidence: 89%
See 1 more Smart Citation
“…In line with this idea, the results of Study 4 revealed that overcompensation is just as effective as equal compensation to promote the preservation of the relationship between the perpetrator and the victim, to increase victims' intentions to cooperate with the perpetrator again in the future, and to entail actual cooperative behavior on the part of the victim. These results also corroborate the findings of a recently conducted meta-analysis in the field of consumer behavior, which demonstrated that overcompensation has no additional effect on post-complaint satisfaction, beyond the impact of simple compensation (Gelbrich & Roschk, 2011).…”
Section: Economic and Psychological Perspectivessupporting
confidence: 89%
“…This implies that overcompensation should yield similar (no better, nor worse) results as equal compensation. Accordingly, research in the area of consumer behavior recently confirmed the idea that overcompensation is of little additional value in a meta-analysis of 17 experimental studies (Gelbrich & Roschk, 2011) by showing that overcompensation does not significantly enhance post-complaint satisfaction beyond the effect of simple compensation (i.e., when the refund given is equivalent to or less than the purchase price).…”
Section: A Psychological Perspective On Overcompensationmentioning
confidence: 98%
“…Particularly interesting in this regard is that the previously mentioned work of Haesevoets, Van Hiel, Onraet, et al () on low‐price guarantees showed, across a set of four empirical studies, that overcompensating price differences in fivefold is not more effective to enhance customer loyalty than equally compensating price differences. In line with the results of this recent study (and those of various other compensation studies; e.g., see Estelami & De Maeyer, ; Garrett, ; Haesevoets, Van Hiel, Pandelaere, et al, ; Noone & Lee, ; for a meta‐analysis, see Gelbrich & Roschk, ; for a recent field study, see Goode, Hoehle, Venkatesh, & Brown, ), the present findings indicated that, in general, large overcompensation does not improve customer loyalty beyond the level that is already reached by equal compensation. Given the high incremental costs of large overcompensation and its lack of positive effects, overcompensation can be considered a cost‐ineffective business strategy for companies to enhance loyalty.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, Boshoff (1999) found in the context of an airline company that a refund of expenses plus an additional free airline ticket enhanced customers' satisfaction more than when merely the expenses were reimbursed. A similar positive effect of receiving overcompensation was obtained in the context of a hotel (Gilly & Hansen, 1985) and a restaurant (Hocutt, Bowers, & Donavan, 2006).…”
supporting
confidence: 59%
“…In this light, it should be noted that in the present study we only tested and found the mediating role of fairness perceptions for the largest price-beating condition that covered price differences five times. We did this because prior research on overcompensation has revealed that people can handle unfairness, at least when it is not too large and in their advantage (e.g., see Boshoff, 1997;Gilly & Hansen, 1985;Hocutt et al, 2006). Based on these findings, it can thus reasonably be expected that a price-beating refund (and thus the degree of advantageous inequality) has to be rather large in order to be perceived as less fair than price-matching (which restores the state of equality).…”
Section: Theoretical Implicationsmentioning
confidence: 99%